Genome‐wide single nucleotide polymorphism‐based assay for high‐resolution epidemiological analysis of the methicillin‐resistant Staphylococcus aureus hospital clone EMRSA‐15. (9th August 2013) - Holmes, A.; McAllister, G.; McAdam, P. R.; Hsien Choi, S.; Girvan, K.; Robb, A.; Edwards, G.; Templeton, K.; Fitzgerald, J. R.; Lina, G.
Abstract The EMRSA‐15 clone is a major cause of nosocomial methicillin‐resistant Staphylococcus aureus (MRSA) infections in the UK and elsewhere but existing typing methodologies have limited capacity to discriminate closely related strains, and are often poorly reproducible between laboratories. Here, we report the design, development and validation of a genome‐wide single nucleotide polymorphism (SNP) typing method and compare it to established methods for typing of EMRSA‐15. In order to identify discriminatory SNPs, the genomes of 17 EMRSA‐15 strains, selected to represent the breadth of genotypic and phenotypic diversity of EMRSA‐15 isolates in Scotland, were determined and phylogenetic reconstruction was carried out. In addition to 17 phylogenetically informative SNPs, five binary markers were included to form the basis of an EMRSA‐15 genotyping assay. The SNP‐based typing assay was as discriminatory as pulsed‐field gel electrophoresis, and significantly more discriminatory than staphylococcal protein A (spa) typing for typing of a representative panel of diverse EMRSA‐15 strains, isolates from two EMRSA‐15 hospital outbreak investigations, and a panel of bacteraemia isolates obtained in healthcare facilities in the east of Scotland during a 12‐month period. The assay is a rapid, and reproducible approach for epidemiological analysis of EMRSA‐15 clinical isolates in Scotland. Unlike established methods the DNA sequence‐based method is ideally suited for inter‐laboratory comparison of identified genotypes, and its flexibility lends itself to supplementation with additional SNPs or markers for the identification of novel S. aureus strains in other regions of the world.